Pharmacokinetics and synovial fluid concentrations of flurbiprofen enantiomers in horses: chiral inversion - Soraci, Alejandro Luis (2005)
Flurbirpofen (FBP), a member of the 2-aryl propionate nonsteroidal anti-inflammatory drug class, has potent anti-inflammatory and analgesic properties. The commercial preparation is a racemic mixture of the R(−) and S(+) enantiomers of FBP. In this study, R(−) and S(+) FBP were used to investigate the metabolic chiral inversion. Each enantiomer was administered separately (0.25 mg/kg) and in a racemic mixture (0.5 mg/kg) intravenously to horses. Plasma and synovial concentration of each enantiomer was determined and the disposition of each was analyzed. After intravenous administration of R(−) FBP and S(+) FBP to horses no chiral inversion was detected. After the administration of the FBP racemate and individual enantiomers no differences were observed between pharmacokinetic parameters [t1/2â (h), Cl (L/h·kg), AUC (ìg·h/mL), Vss (L/kg) and MRT (h)] for R(−) and S(+) FBF. Synovial fluid concentrations of both FBP enantiomers were lower than plasma concentrations and no stereoselective differences were detected. These data indicate that the disposition of FBF in horses is not enantioselective and demonstrate a difference in the pharmacokinetic behavior of the enantiomers as compared with other 2-aryl-propionic acids, such as carprofen, ketoprofen and vedaprofen in the horse.